2019
DOI: 10.3390/molecules24173075
|View full text |Cite
|
Sign up to set email alerts
|

Rice Husk Hydrolytic Lignin Transformation in Carbonization Process

Abstract: Lignin processing products have an extensive using range. Because products properties depend on lignin precursor quality it was interesting to study lignin isolated from rice husk being a large tonnage waste of rice production and its structural transformations during carbonization. Lignin isolated by the thermal hydrolysis method with H2SO4 1 wt % solution and its carbonized products prepared under different carbonization conditions were characterized using elemental analysis, IR, TPD-MS, XRD, TEM, and EPR. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…The pyrolysis stage with T max ~350 °C occurs due to the degradation of aromatic compounds of lignin, which proceeds in a wider temperature range with the formation of phenol ( m / z = 94, T max = 350 °C), pyrocatechol ( m / z = 110, T max = 290–330 °C), cresols ( m / z = 107, T max = 365 °C), tropylium ion, C 7 H 7 + ( m / z = 91, T max = 340 °C), 4-vinyl-methylguaiacol ( m / z = 164, T max = 290 °C), benzene ( m / z = 78, T max = 360, 545 °C), naphthalene ( m / z = 128, T max = 520 °C), and 4-vinylphenol ( m / z = 120, T max = 220, 290 °C). The formation of these compounds is caused by thermal transformations of corresponding aromatic links and functional groups of lignin [ 35 ]. The stage with T max ~200 °C corresponds to the destruction of hemicelluloses [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pyrolysis stage with T max ~350 °C occurs due to the degradation of aromatic compounds of lignin, which proceeds in a wider temperature range with the formation of phenol ( m / z = 94, T max = 350 °C), pyrocatechol ( m / z = 110, T max = 290–330 °C), cresols ( m / z = 107, T max = 365 °C), tropylium ion, C 7 H 7 + ( m / z = 91, T max = 340 °C), 4-vinyl-methylguaiacol ( m / z = 164, T max = 290 °C), benzene ( m / z = 78, T max = 360, 545 °C), naphthalene ( m / z = 128, T max = 520 °C), and 4-vinylphenol ( m / z = 120, T max = 220, 290 °C). The formation of these compounds is caused by thermal transformations of corresponding aromatic links and functional groups of lignin [ 35 ]. The stage with T max ~200 °C corresponds to the destruction of hemicelluloses [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since the structure of this natural polymer is extremely complex, model compounds are often used to study its conversion to high value-added chemicals [8,10]. Ferulic and vanillic acids, as well as pyrocatechol and guaiacol are common products of lignin processing [1,8,[11][12][13], and therefore are often used as model lignin compounds [4,8,11,[14][15][16][17]. These compounds are lignin structural units of various sizes and contain almost the entire list of functional groups present in the lignin macromolecule.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this is that, at a higher carbonisation temperature, more acid and/or volatile substances will evaporate from the sample, thereby reducing the carbon yield. 50 Yefremova et al 53 proposed that the decrease in the yield of carbonised products at higher pyrolysis temperatures may be due to the increase in the primary decomposition of the precursor and the increase in the secondary decomposition of the formed carbon material. Mussatto et al 49 , Hayashia et al 54 and Wu et al 55 reported similar results from biomass materials.…”
Section: Effects Of Process Parameters On Ac Yield Bet Surface Area A...mentioning
confidence: 99%